Climate Variability and Communities' Vulnerability along Ghana's Coastline - Poku-Boansi, M.; Amoako, C.; Owusu-Ansah, J.K.; Cobbinah, P.B. (Ghana Social Science Journal, 2020)
Over the last three decades, communities along Ghana's coastline have been affected by storm surges, coastal floods and erosion from relatively less predictable hydro meteorological hazards and disasters. Using selected coastal communities in the Keta municipality, this study explores the vulnerabilities of coastal communities in Ghana and the effectiveness of emerging adaptation interventions. Evidence for the study was gathered through a review of relevant secondary documents: a household survey: focus group discussions and institutional consultations. The paper reveals several hydro meteorological risks (e.g., shoreline erosion, storm surges) which threaten the inundation of some communities and the destruction of infrastructure and coastal resources. While there is evidence of adaptive governance in terms of institutional efforts (construction of sea defence wall), there is limited state commitment towards climate change adaptation and poor local community engagement. State interventions require co-ordinated and sustained efforts from national and local level institutions to ensure adaptation and resilience to coastal vulnerability.
Ghana Social Science Journal, 17(1), 108-130
Keywords: Climate Hazards; Resilience; Adaptation; Adaptive Governance; Vulnerability